2020
DOI: 10.1091/mbc.e20-05-0341
|View full text |Cite
|
Sign up to set email alerts
|

The Borealin dimerization domain interacts with Sgo1 to drive Aurora B–mediated spindle assembly

Abstract: The Chromosomal Passenger Complex (CPC), which includes the kinase Aurora B, is a master regulator of meiotic and mitotic processes that ensure the equal segregation of chromosomes. Sgo1 is thought to play a major role in the recruitment of the CPC to chromosomes, but the molecular mechanism and contribution of Sgo1-dependent CPC recruitment is currently unclear. Using Xenopus egg extracts and biochemical reconstitution, we found that Sgo1 directly interacts with the dimerization domain of the CPC subunit Bore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 67 publications
6
14
0
Order By: Relevance
“…(3) consistent with previous findings (Bonner et al, 2020), the N-terminal coiled-coil also contacts the Borealin dimerisation domain; and (4) the Sgo1 region beyond the N-terminal coilcoil region, which is predicted to be unstructured, contacts both Survivin and Borealin with most contacts confined to the Sgo1 central region spanning amino acids (aa) 180-300 (Fig. 2A and 2B).…”
Section: Sgo1 Makes Multipartite Interactions With Cpc Subunitssupporting
confidence: 89%
See 1 more Smart Citation
“…(3) consistent with previous findings (Bonner et al, 2020), the N-terminal coiled-coil also contacts the Borealin dimerisation domain; and (4) the Sgo1 region beyond the N-terminal coilcoil region, which is predicted to be unstructured, contacts both Survivin and Borealin with most contacts confined to the Sgo1 central region spanning amino acids (aa) 180-300 (Fig. 2A and 2B).…”
Section: Sgo1 Makes Multipartite Interactions With Cpc Subunitssupporting
confidence: 89%
“…Haspin mediates phosphorylation on histone H3 Thr3 (H3T3ph), which is recognised by the BIR domain of Survivin (Jeyaprakash et al, 2011;Kelly et al, 2010;Wang et al, 2010). Bub1 phosphorylates Thr120 of Histone H2A (H2AT120ph) (Bonner et al, 2020;Tsukahara et al, 2010;Wang et al, 2010;Yamagishi et al, 2010) that is recognised by Sgo1 which in turn, is suggested to interact with Borealin via its coiled-coil domain (Bonner et al, 2020;Yamagishi et al, 2010). However, our earlier work showed that Sgo1 N-terminal tail (AKER peptide) can also interact with Survivin BIR domain using a binding mode that is nearly identical to that of the histone H3 tail phosphorylated at Thr3 (Jeyaprakash et al, 2011), suggesting that a direct interaction between Survivin and Sgo1 could also be possible.…”
Section: Introductionmentioning
confidence: 99%
“…At the centromere, PP2A-B56α localization is dependent on Sgo2, not on Sgo1 (Vallardi et al, 2019). Interestingly, however, Sgo1 also binds the CPC via Borealin, and a Borealin-Sgo1-PP2AC complex was reconstituted in vitro from recombinant proteins (Bonner et al, 2020). Together, these data suggest that Sgo1 may coordinate to allow PP2A-B56 to antagonize CPC-based Aurora B activity at the centromere (Meppelink, Kabeche, Vromans, Compton, & Lens, 2015;Vallardi et al, 2019) and inner kinetochore (Suijkerbuijk et al, 2012;Xu et al, 2013).…”
Section: Phosphatases In Mitotic Spindle Assemblymentioning
confidence: 89%
“…GeneMANIA analysis showed twenty neighboring genes to CDCAs , and the functions of these genes are also related to cell cycle regulation. For example, SGO1 is considered to play a major role in recruiting the chromosomal passenger complex to chromosomes ( Bonner et al, 2020 ); SGO2 is a pericentromeric protein that associates with cohesin at centromeres and regulates chromosomal segregation during meiosis ( El et al, 2017 ). SGO1/2 functions as an essential protector for centromeric cohesion and is required for accurate chromosome segregation during mitosis and meiosis ( Dudas et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%